Penerapan Metode Quality Function Deployment (QFD) Dalam Upaya Meningkatkan Kualitas Produk Es Kopi Susu di Coffee Shop ABC - Chelseanna, Dea; Yuarini, Dewa Ayu Anom; Satriawan, I Ketut (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Overall sales at Coffee Shop ABC decreased by 21% from January to May 2023. One factor contributing to this decline is the presence of similar coffee shop competitors in close proximity. The aim of this research is to determine product attributes, analyze the level of importance and satisfaction of the product, and determine strategies to improve product quality. The method used in this research is Quality Function Deployment (QFD) and the variables used are the quality attributes of the iced coffee milk product, namely price, taste, aroma, color, physical appearance, temperature and volume. Based on the QFD analysis, it was found that the product quality attribute with the highest importance value was the volume attribute (4.61), the attribute that received the highest satisfaction value was taste (4.29), and the strategy to improve product quality that could be recommended was to carry out an evaluation every month to determine achievements. product targets and shortcomings.